Weblog : an alternative platform to deliver formal lifelong learning - Nantha Kumar Subramaniam (2014)
Weblogs (or blogs) usually contain diary style content, with updates posted on a regular basis and displayed in reverse chronological order controlled by a single author. The blogs can be publicly accessed by anyone or by invitation from the blog’s author. The content or use of a blog is the choice of the author and may include news, updates, articles, and reflections. The small but developing literature on web logging underscores its potential as an effective learning resource for use in higher education. Some advantages of blog for learning include assisting students to become subject-matter experts through a process of regular scouring, filtering and posting, increasing student interest and ownership in learning, giving students legitimate chances to participate and acculturating them into a community of practice and providing opportunities for diverse perspectives. However, the use of the blog for formal lifelong learning is very much limited as the open universities prefer to use their own learning management systems or other online platforms to deliver the teaching and learning activities. This paper contributes to these discussions through a case study of the author's experience with the on-going development of an educational blogging resource for use in an undergraduate IT subject. Using the instructional strategy of independent study and indirect instruction to support the learner-centered pedagogies, the author believe the elements of content, interactivity, collaboration and assessment are the pillars to make an education-based blog for adult learners to support their self-managed learning. Detailing the theoretical aims, design, implementation and students’ evaluation of the blog, the paper puts forward the argument for the educational use-value of blogging as a platform to support self-managed learning for adult learners in the formal lifelong learning environment. (Abstract by author)